Geoelectric studies of the south Voronezhcrystalline massif - I. Logvinov; V. I. Tregubenko; V. N. Tarasov (Геофизический журнал, 2014)
The first results of interpretation of magnetic variation data, focused on the three profiles in the southern part of the Voronezh crystalline massif by the two-dimensional inversion have been pre-sented. Several objects of low resistance, the roof of which is located at the depth of less than 10 km have been subdivided. The most reliable object spatially correlates with the Belgorod-Mikhailovsk greenstone belt (and the spread of ferruginous quartzites of the Kursk Magnetic Anomaly).